The computation of generalized Ehrhart series in Normaliz. (May 2015) - Bruns, Winfried; Söger, Christof
Abstract: We describe an algorithm for the computation of generalized (or weighted) Ehrhart series based on Stanley decompositions as implemented in the offspring NmzIntegrate of Normaliz. The algorithmic approach includes elementary proofs of the basic results. We illustrate the computations by examples from combinatorial voting theory.